2022
DOI: 10.1177/20406223221078672
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy interventions may relieve pain in individuals with central neuropathic pain: a systematic review and meta-analysis of randomised controlled trials

Abstract: Objectives: To evaluate the effectiveness of any form of physiotherapy intervention for the management of central neuropathic pain (cNeP) due to any underlying cause. Methods: Multiple databases were searched from inception until August 2021. Randomised controlled trials evaluating physiotherapy interventions compared to a control condition on pain among people with cNeP were included. Methodological quality and the quality of evidence were assessed using the Physiotherapy Evidence Database Scale and the Gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 74 publications
(218 reference statements)
0
3
0
Order By: Relevance
“…However, it may not eliminate the pain completely, and success rates vary. Some studies have reported significant reductions in pain intensity for a subset of patients [58,59]. Mirror therapy utilizes the reflection of the intact limb in a mirror to create the illusion of the missing limb's presence.…”
Section: Adjuvant Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…However, it may not eliminate the pain completely, and success rates vary. Some studies have reported significant reductions in pain intensity for a subset of patients [58,59]. Mirror therapy utilizes the reflection of the intact limb in a mirror to create the illusion of the missing limb's presence.…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…It is believed to balance the flow of energy and promote healing. Acupuncture has been explored as a potential therapy for phantom limb pain, and some individuals have reported reduced pain levels and improved overall well-being after acupuncture sessions [59,61]. The success rates of acupuncture vary among…”
Section: Adjuvant Therapymentioning
confidence: 99%
See 1 more Smart Citation